2018
DOI: 10.1128/iai.00016-18
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role for Regulatory B Cells as a Major Source of Interleukin-10 in Spleen from Plasmodium chabaudi-Infected Mice

Abstract: Interleukin-10 (IL-10)-producing regulatory B (Breg) cells were found to be induced in a variety of infectious diseases. However, its importance in the regulation of immune response to malaria is still unclear. Here, we investigated the dynamics, phenotype, and function of Breg cells using AS-infected C57BL/6 and BALB/c mice. BALB/c mice were more susceptible to infection and had a stronger IL-10 response in spleen than C57BL/6 mice. Analysis of the surface markers of IL-10-producing cells with flow cytometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 63 publications
(67 reference statements)
1
22
0
Order By: Relevance
“…The study conducted on Plasmodium chabaudi infected C57BL/6 and BALB/c mice shows that CD19 + CD5 + CD1d hi cells are the well-established Breg subset though represented for less than 20% of IL-10 secreting B cells in both strains during infection. 46 Though the roles of Breg cells during uncomplicated and complicated human malaria are yet to be further investigated, available evidence have shown that Breg cells have a beneficial role in severe malaria via preventing the worsening of inflammatory responses by cytotoxic T cells. 47 Thus, for neuronal disorder due to sequestration of erythrocytes, Breg cells and anti-inflammatory cytokines, such as IL-10, are found to be important in inhibiting the neuro-pathogenesis of malaria.…”
Section: Malariamentioning
confidence: 99%
“…The study conducted on Plasmodium chabaudi infected C57BL/6 and BALB/c mice shows that CD19 + CD5 + CD1d hi cells are the well-established Breg subset though represented for less than 20% of IL-10 secreting B cells in both strains during infection. 46 Though the roles of Breg cells during uncomplicated and complicated human malaria are yet to be further investigated, available evidence have shown that Breg cells have a beneficial role in severe malaria via preventing the worsening of inflammatory responses by cytotoxic T cells. 47 Thus, for neuronal disorder due to sequestration of erythrocytes, Breg cells and anti-inflammatory cytokines, such as IL-10, are found to be important in inhibiting the neuro-pathogenesis of malaria.…”
Section: Malariamentioning
confidence: 99%
“…Bregs can be divided into Bregs producing IL10 (Br1), Bregs producing TGFß (Br3) and FoxP3 expressing Bregs (BFoxP3) [104]. The most studied ones in malaria are Br1, which include all B cells producing IL10 [105,106]. Br1 are mostly found in the spleen and the peritoneal cavity, but a small proportion of them circulates in the blood together with an accessory B cell population with the potential capacity to become Br1 [104].…”
Section: Regulatory B Cellsmentioning
confidence: 99%
“…In contrast, in other Bregs, such as Br3, despite promoting Treg by TGFβ production, the same cytokine drives Br3 apoptosis, self-controlling Br3 proliferation [104]. In fact, B cells are suggested to be as important as T cells in IL10 production, as seen in murine malaria [105].…”
Section: Regulatory B Cellsmentioning
confidence: 99%
“…Human B cells exposed to Leishmaniasis infantum amastigotes exhibited a regulatory phenotype (CD19 + CD24 + CD27 − ) and higher capacity to produce IL‐10 108 . Furthermore, during a Plasmodium chabaudi chabaudi infection in mice, B cells were the main IL‐10‐producing cells, most were identified as IgG + B cells but only 20% of these cells were part of the Breg subset CD19 + CD5 + CD1d hi 109 …”
Section: How To Induce Breg Cellsmentioning
confidence: 99%